KUALITAS ROHANI MENURUT ROMA 12:11 DAN IBADAH DARING DENGAN PERTUMBUHAN IMAN - Yohanes Kurniawan; Andreas E. Nugroho (The Way: Jurnal Teologi dan Kependidikan, 2023)
The COVID-19 pandemic experienced by the Indonesian people has had an impact on several aspects, and one of them is the worship activities of all religions in general and Christianity in particular. All worship meetings must be conducted online and cannot be face-to-face. This triggers a considerable influence on the growth of the congregation at CMC Gate Pujian Jakarta. Instead of growing, the number of congregations in this church is actually decreasing. In addition to the influence of online worship, it turns out that the spiritual quality of the workers and servants in the church is also a factor that influences it. Therefore, through quantitative methods, the researc tries to examine the relationship spiritual quality meetings and online worship on the growth of the number of congregations at CMC Gerbang Pujian Jakarta. It was found that the relationship between spiritual quality and online worship has a positive, strong and unidirectional value with congregational growth.